FENOMENOLOGI PENGALAMAN MAHASISWA BARU DALAM MENGHADAPI KONDISI PEMBELAJARAN PERKULIAHAN DI KELAS MPI A - Annisa Nur Qomariyah; Ifa Mirotul Aini; Septiana Al-Izzatun Ramadhani; Titian Intania Putri (STKIP Pesisir Selatan, 2026)
This study aims to determine and understand the experiences of new students in facing learning conditions in the MPI A class. The study used a qualitative approach with a phenomenological method to explore the meaning of students' subjective experiences. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study indicate that new students experience various challenges in the learning process, such as differences in learning systems from school to college, difficulty understanding material due to rote-based learning habits, and low engagement in learning due to personality factors such as shyness. In addition, students develop independent learning strategies, such as repeated reading to understand the material. On the other hand, the learning process also contributes to character formation, particularly in increasing a sense of responsibility and discipline. Overall, the new student experience is interpreted as a process of adaptation and self-development that encompasses academic, social, and personal aspects.